2020
DOI: 10.1080/14787210.2021.1846520
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes in adult patients hospitalized with influenza, respiratory syncytial virus and human metapneumovirus infections

Abstract: Zhang (2020): Clinical characteristics and outcomes in adult patients hospitalized with influenza, respiratory syncytial virus and human metapneumovirus infections, Expert Review of Anti-infective Therapy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
20
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 48 publications
11
20
3
Order By: Relevance
“…Relative to patients without CVEs, those with CVEs were more likely to suffer from hypertention (31.1% vs 24.3%, p = 0.021), coronary artery disease (42.3% vs 18.8%, p < 0.001), preexisting heart failure (7.8% vs 1.8%, p < 0.001), cerebrovascular disease (13.7% vs 8.2%, p = 0.006), and chronic kidney disease (7.2% vs 1.6%, p < 0.001). Mental confusion (35.2% vs 7.1%, p < 0.001), respiratory rates ≥ 30 breaths/min (25.6% vs 9.4%, p < 0.001), leukocyte counts > 10×10 9 /L (30.4% vs 24.5, p = 0.046), lymphocytes < 0.8×10 9 /L (83.3% vs 33.3%, p < 0.001), hemoglobin (HB) levels < 100 g/L (39.9% vs 17.5%, p < 0.001), blood urea nitrogen (BUN) > 7 mmol/L (65.9% vs 33.3%, p < 0.001), and PaO 2 /FiO 2 < 300 mmHg (54.9% vs 45.4, p = 0.005) at time of admission were more frequently observed in patients with CVEs than in patients without CVEs. Patients with CVEs were more likely to be treated with systemic corticosteroids (50.9% vs 15.8%, p < 0.001), ACEIs/ARBs (54.6% vs 35.4%, p < 0.001), statins (54.9% vs 37.0%, bp < 0.001), anticoagulants (19.1% vs 7.1%, p < 0.001), and β-receptor blockers (27.6% vs 16.5%, p < 0.001), and were less likely to have undergone early NAI therapy (15.4% vs 43.7%, p < 0.001) (Table 1 2).…”
Section: Risk Factors Associated With Cve Incidence In Flu-p Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to patients without CVEs, those with CVEs were more likely to suffer from hypertention (31.1% vs 24.3%, p = 0.021), coronary artery disease (42.3% vs 18.8%, p < 0.001), preexisting heart failure (7.8% vs 1.8%, p < 0.001), cerebrovascular disease (13.7% vs 8.2%, p = 0.006), and chronic kidney disease (7.2% vs 1.6%, p < 0.001). Mental confusion (35.2% vs 7.1%, p < 0.001), respiratory rates ≥ 30 breaths/min (25.6% vs 9.4%, p < 0.001), leukocyte counts > 10×10 9 /L (30.4% vs 24.5, p = 0.046), lymphocytes < 0.8×10 9 /L (83.3% vs 33.3%, p < 0.001), hemoglobin (HB) levels < 100 g/L (39.9% vs 17.5%, p < 0.001), blood urea nitrogen (BUN) > 7 mmol/L (65.9% vs 33.3%, p < 0.001), and PaO 2 /FiO 2 < 300 mmHg (54.9% vs 45.4, p = 0.005) at time of admission were more frequently observed in patients with CVEs than in patients without CVEs. Patients with CVEs were more likely to be treated with systemic corticosteroids (50.9% vs 15.8%, p < 0.001), ACEIs/ARBs (54.6% vs 35.4%, p < 0.001), statins (54.9% vs 37.0%, bp < 0.001), anticoagulants (19.1% vs 7.1%, p < 0.001), and β-receptor blockers (27.6% vs 16.5%, p < 0.001), and were less likely to have undergone early NAI therapy (15.4% vs 43.7%, p < 0.001) (Table 1 2).…”
Section: Risk Factors Associated With Cve Incidence In Flu-p Patientsmentioning
confidence: 99%
“…Influenza virus causes an estimated 15-20% of CAP cases, with over 3-5 million cases and 290,000-650,000 deaths globally each year. 8 Severe influenza infections result in pneumonia in over half of affected patients, 9 and such influenza-associated pneumonia (Flu-p) can additionally cause multiple organ dysfunction. Time-series analyses have shown that CVE rates are elevated during and immediately following influenza epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to patients without CVEs, those with CVEs were more likely to suffer from hypertention (31.1% vs 24.3%, p = 0.021), coronary artery disease (42.3% vs 18.8%, p < 0.001), preexistingheart failure (7.8% vs 1.8%, p < 0.001), cerebrovascular disease (13.7% vs 8.2%, p = 0.006), and chronic kidney disease (7.2% vs 1.6%, p < 0.001). Mental confusion (35.2% vs 7.1%, p < 0.001), respiratory rates ≥ 30 breaths/min (25.6% vs 9.4%, p < 0.001), leukocyte counts > 10×10 9 /L (30.4% vs 24.5, p = 0.046), lymphocytes < 0.8×10 9 /L (83.3% vs 33.3%, p < 0.001), hemoglobin (HB) levels < 100 g/L (39.9% vs 17.5%, p < 0.001), blood urea nitrogen (BUN) > 7 mmol/L (65.9% vs 33.3%, p < 0.001), and PaO 2 /FiO 2 < 300 mmHg (54.9% vs 45.4, p = 0.005) at time of admission were more frequently observed in patients with CVEs than in patients without CVEs. Patients with CVEs were more likely to be treated with systemic corticosteroids (50.9% vs 15.8%, p < 0.001), ACEIs/ARBs (54.6% vs 35.4%, p < 0.001), statins (54.9% vs 37.0%,bp < 0.001), anticoagulants (19.1% vs 7.1%, p < 0.001), and β-receptor blockers (27.6% vs 16.5%, p < 0.001), and were less likely to have undergone early NAI therapy (15.4% vs 43.7%, p < 0.001) (Table 1).…”
Section: Risk Factors Associated With Cve Incidence In Flu-p Patientsmentioning
confidence: 99%
“…In uenza virus causes an estimated 15-20% of CAP cases, with over 3-5 million cases and 290,000-650,000 deaths globally each year [8]. Severe in uenza infections result in pneumonia in over half of affected patients [9], and such in uenza-associated pneumonia (Flu-p) can additionally cause multiple organ dysfunction. Time-series analyses have shown that CVE rates are elevated during and immediately following in uenza epidemics [10].…”
Section: Introductionmentioning
confidence: 99%
“…In uenza is a common viral respiratory disease that affects between 5% and 10% of the world's population each year, resulting in roughly 3-5 million severe infections and 290,000 -650,000 annual deaths [1][2]. In uenza-related pneumonia (Flu-p) is a severe form of in uenza infection associated with over 50% of in uenza-related hospitalizations [3][4].…”
Section: Introductionmentioning
confidence: 99%